EMIGRATION AND ITS GEODEMOGRAPHIC IMPACT IN SLĂNIC MOLDOVA CITY OF BACĂU COUNTY, ROMANIA - MORARU, Andreea; MUNTELE, I. (Studia Universitatis Babeș-Bolyai Geographia, 2015)
Emigration and Its Geodemographic Impact in Slănic Moldova City of Bacău County, Romania. The article talks about emigration from Slănic Moldova, a city from Bacău county, Romania, and its geodemographic impact, using statistical data from Population Censuses, National Statistics Institute and the own survey conducted in January-April 2015. The study starts with an analysis concerning the amplitude of emigration, in the second part, trying to highlight its importance in the numerical evolution of the population from Slănic Moldova. The third part brings forward the problem of emigration by age and gender, which give a clear view over the situation present in the city mentioned. Using eloquent data, the study show up the demographic changes trying to see to what extent emigration had a contribution to it. To reduce the syncope of a descriptive analysis, the collected data are outlined through cartographic method in order to show the geographical distribution of emigration in the city.